Experimental Study of the Principal Characteristics of Sustainable Micropile Grout Containing Alternative Sands - Phuc Lam, Dao; Van Manh, Nguyen; Nhan, Pham Thi; Viet, Le Huy; Lam, Tang Van; Van Phi, Dang; Hung, Ngo Xuan; Osinski, Piotr; Onyelowe, Kennedy C.; Van Duc, Bui (Civil Engineering Journal, 2024)
The paper discloses a laboratory investigation on employing manufactured sand cement as grout in micropiling works. In practice, to prepare micropile grouts, Portland cement is commonly used. The grout usually consists of natural sand to obtain the strength parameters and value international standards require for micropile construction. It is common knowledge that using concrete and natural sand leaves its environmental footprint. Although there have been numerous attempts to use more environmentally friendly materials, utilizing manufactured sands, particularly for micropile grouting, is a scientific challenge that researchers are still trying to address. The present study investigates the performance of micropile grout mixtures containing manufactured (M) sands, including limestone (L-M) and granite (G-M) rock as replacements for natural sand. For this purpose, laboratory tests, including unconfined compression strength (UCS) and workability tests, were conducted on samples with varying compositions and ratios of L-M and G-M materials. The complementary microstructure and chemical composition analyses were performed using scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDS) analysis. The laboratory results indicate that the UCS at 28 days of hardening for all M-sand cement mixtures exceeds the minimum standards required values, falling in a range of 40-50.2 MPa. It’s noteworthy that the strength of cement grout containing L-M sand was found to be higher than that of G-M sand. The SEM results show the G-M sand grain is rougher than L-M, and the L-M sand grain size is finer than the G-M samples, which causes a decrease in porosity at the interfacial transition zone. Grout workability tests demonstrated that higher water-cement ratios (W/C) led to increased fluidity across all mixtures, with G-M sand resulting in lower flowability than L-M samples. Overall, the results suggest that the proposed mixtures could serve as sustainable alternatives for micropiling, reducing cement content and utilizing alternative, reused materials in grouting mixtures more effectively and sustainably. Doi: 10.28991/CEJ-2024-010-10-019 Full Text: PDF